Compositor e intérprete: reflexões sobre colaboração e processo criativo em Caminho Anacoluto II – quasi-Vanitas de Marcílio Onofre - Lobo, Rodrigo de Almeida Eloy (2016)
A survey about the work written by the composer Marcílio Onofre (1982), this research discusses the collaborative process between the composer and the performer in Caminho Anacoluto II – quasi-Vanitas for violin and piano. We will discuss about the process of technical expansion that occurs in contemporary music and the results in the music of this period. We will also introduce a brief presentation of the composer, the Laboratory of Musical Composition, Onofre’s participation on it and the collaborations that occurred. Finally, an approach to the work Caminho Anacoluto II – quasi-Vanitas, its structural aspects and a reflection on the collaborative process.